EVALUATION OF TOFU PRODUCT BUSINESS PROJECTS IN THE ERA OF BUSINESS COMPETITION 5.0 - Karina Utami Anastuti; Kharisma A frilia; Shofiyana Eli Irmawati; Shifani Orchida Rahman; Febriana Nur Khamidah; Anisa Valentina; Firhaq Finanda LN (International Journal of Entrepreneur and Business Administration, 2023)
The purpose of this research is to find out the feasibility study of Mr. Sudibyo's Tofu Business in terms of management, financial, legal, environmental, marketing, technical, and socio-economic aspects. The type of research used in this research is mixed research methods. The mixed method used is qualitative and quantitative research, which is more dominated by qualitative research. Data collection techniques used in this study were interviews, observation, documentation, and literature study. The results of the analysis of this study indicate that in terms of Mr. Sudibyo's Tofu Business in terms of the seven aspects it can be said to be feasible because Mr. Sudibyo's Tofu Business has fulfilled several aspects of the eligibility criteria for a business.